Trajetórias de jovens negros egressos do ensino superior e desigualdade social - Paula, Simone dos Reis de (2017)
This research to verify the social and educational trajectory of five blacks graduated from the University of Zumbi dos Palmares, specifically the Bussiness Administration course. We sought to verify how the social and scholastic trajectory of these graduates occurred, the choice of the course undertaken, Business Administration. This course made possible their professional and social insertion? For that, the social and school trajectory of five graduates belonging to the Business Administration course of the years 2010 to 2014 was verified and analyzed, being this the focus of the research. The research procedure to achieve this focus was the interview. The purpose of the analysis was to verify if the course of Business Administration really brought the contribution sought by these graduates, enabling social, professional and economic success. The objectives of this research were to characterize the subjects regarding their socioeconomic conditions, to investigate the social and educational trajectory of five graduates from the years 2010 to 2014 of the conclusion of the Business Administration course of the higher education institution Zumbi dos Palmares, and the reasons that led them to choose this course and this private institution and to verify from the perspective of the five graduates, if the course of Business Administration contributed to achieve professional, social and economic success. The authors employed in the work are Bourdieu and Lahire, and their remarkable concepts: cultural capital, social capital, social space and family configurations, respectively. In addition to them the concepts of Munanga, race, racism and racial prejudice. The five interviews answered the problem and the proposed objectives. Finally, the survey indicates that the five interviewees admitted that graduation in the Business Administration course contributed to their achieving a certain social ascension. On the other hand, it proves the idea that these graduates did not have the socioeconomic conditions to enter another course, because they were black, because they did not attend the best schools in basic education, therefore they did not have free choice of courses in Higher Education. These conditions lead them to attend the course of Business Administration, known as the course that quickly places the subjects in the job market